The effect of contrast-temperature water therapy on performance recovery of rugby players - Hamlin, M.; Sheen, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study investigated the effect of contrast-temperature water therapy on elite rugby players' ability to recover after a repeated sprint test.